THU0045 Epratuzumab, an Antibody Targeting CD22 on B Cells, Induces Phosphoprotein Changes Following B-Cell Receptor Activation in Vitro. (23rd January 2014) - Lumb, S.; Torbett, N.; Vendrell, I.; Turner, H.; Page, M.; Hales, P.; Maloney, A.; Vanhaesebroeck, B.; Cutillas, P.; Shock, A.
Abstract : Background: Epratuzumab is a monoclonal antibody targeting CD22 that is currently in phase III clinical trials in systemic lupus erythematosus (SLE) patients. CD22 is found almost exclusively on B cells, and in in vitro B-cell cultures, epratuzumab down-regulates B-cell receptor (BCR)-dependent cell signaling and B-cell activation events 1, 2 . Objectives: To construct a B-cell phosphopeptide library using a recently developed LC-MS/MS methodology (TIQUAS™ or Targeted Quantification of Cell Signalling) 3, and to investigate epratuzumab-dependent changes in phosphoprotein signals in activated B cells. Methods: B cells of >90% purity were isolated from human tonsils (n=8 donors) and stimulated through the BCR using anti-IgM for 2 minutes with prior pre-incubation with either epratuzumab or an IgG1 isotype control for 1 hour. Immediately following stimulation the cells were pelleted by centrifugation and lysed in a urea-based lysis buffer containing phosphatase inhibitors. The cell lysates were sonicated on ice and quantitated by BCA protein assay. Cell lysates were analysed by Western blot for confirmatory B-cell activation markers, ERK1/2. 500 μg of cell extracts were subject to protease digestion and TiO2 phosphopeptide enrichment. LC-MS-MS phosphoproteomic analysis was performed using a label-free quantification strategy (TIQUAS™). A linear mixed effects statistical model was applied to a library of >4900 distinct quantifiable phosphorylation sites distributed across >1800 distinct proteins. Significantly regulated phosphorylated sites were imported into MetaCore and mapped to canonical pathways for further analysis and interpretation. Results: This study explored the pathways differentially modulated by epratuzumab of which the BCR pathway was the most highly regulated. This analysis was able to identify statistically significantly regulated phosphorylation sites in response to pre-incubation with epratuzumab using an adjusted p-value threshold of <0.05, although the most significant changes generally showed no more than a 2-fold difference from signals induced by BCR stimulation alone. Many of the phosphorylation changes modulated by epratuzumab are novel and warrant further study. Of potential interest is the observed increase in ERK1/2 phosphorylation, although a number of other changes were observed for BCR-specific downstream signals on a broad range of protein family types: adaptor proteins (SHC-1, BLNK), phosphatases (SHP-1, SHIP-1), other kinases (PRKCD), histones (H1) and transcription factors (NFAT). Additionally, there was down-modulation of the phosphorylation of Ser 717 on CD22 itself. Conclusions: Pre-incubation of human tonsil-derived B cells with epratuzumab induced discrete but statistically significant changes in phosphoprotein signals after BCR activation. Such observations may enable a better understanding of how epratuzumab modulates B-cell functions in vitro and possibly in patients with SLE. References: Sieger N, et al. Arth Rheum 2012, in press. Daridon C, et al. Arth Res Ther 2010;12:R204. Alcolea M, et al. Mol Cell Proteomics 2012;11:453–66. Disclosure of Interest: S. Lumb Employee of: UCB Pharma, N. Torbett Employee of: Activiomics Ltd, I. Vendrell Employee of: Activiomics Ltd, H. Turner Employee of: Activiomics Ltd, M. Page Employee of: UCB Pharma, P. Hales: None Declared, A. Maloney: None Declared, B. Vanhaesebroeck Employee of: Activiomics Ltd, P. Cutillas Employee of: Activiomics Ltd, A. Shock Employee of: UCB Pharma